Entanglement in the quantum Game of Life - Ney, Peter-Maximilian; Notarnicola, Simone; Montangero, Simone; Morigi, Giovanna (Physical Review A, 2022)
We investigate the quantum dynamics of a spin chain that implements a quantum analog of Conway's Game of Life. We solve the time-dependent Schrödinger equation starting with initial separable states and analyze the evolution of quantum correlations across the lattice. We report examples of evolutions leading to all-entangled chains and/or to time oscillating entangling structures and characterize them by means of entanglement and network measures. The quantum patterns result in structures quite different from the classical ones, even in the dynamics of local observables. A peculiar instance is a structure behaving as the quantum analog of a blinker, but that has no classical counterpart.
Created from Fastlane, Scopus look-up